Study the Optical Properties of (PMMA-PS-TiO2) Nanocomposite - Mohammed, Musaab Khudhur; Hadi, Alaa Najah; abdulkadhim, Dalal Hassan; Rahid, Maher Hasan; Jassim, Khalid S (IJRDO-Journal of Applied Science, 2017)
In this paper, the effect of titanium oxide nanoparticles on optical properties for (PMMAPS)composite has been studied. The titanium oxide nanoparticles was added to the(PMMA-PS) composite for different weight percentages are (4, 8, 12) wt.%. The opticalproperties were measured in range of wavelength (200-1100) nm. The experimentalresults show that the absorbance of (PMMA-PS) composite was increased with theincrease of titanium oxide concentrations. The optical constants and energy gap werechanged with the addition of titanium oxide nanoparticles concentrations.